Effects of Tootling on Classwide Disruptive and Appropriate Behavior of Upper-Elementary Students. (May 2015) - Lambert, Abigail M.; Tingstrom, Daniel H.; Sterling, Heather E.; Dufrene, Brad A.; Lynne, Shauna
The current study assessed the effects of a positive peer reporting procedure known as Tootling on classwide disruptive as well as appropriate behavior with fourth- and fifth-grade students and their teachers in two regular education classrooms. Tootling is a technique that teaches students to recognize and report peers' prosocial behavior rather than inappropriate behavior (i.e., as in tattling), and is also a variation on the expression, "tooting your own horn." Tootling combined with an interdependent group contingency and publicly posted feedback were assessed using an ABAB withdrawal design with a multiple baseline element across classrooms. Results demonstrated decreases in classwide disruptive behavior as well as increases in appropriate behavior compared with baseline and withdrawal phases across both classrooms, with results maintained at follow-up. Tootling was also rated highly acceptable by both teachers. Effect size calculations reflected moderate to strong effects across all comparisons. Limitations of the present study, directions for future research, and implications for practice are discussed.